Oxidative effect of laser radiation on iron ions in hemoglobin - Raghad Star Karim Abdullah; Zeinab Hassan Salem (Genius Journals, 2023)
Hemoglobin is considered as a main energy receiver from the laser beam, especially at the wavelength of 660nm, to stimulate biological reactions such as the formation of peroxides and reactions that may be attributed to the main cause of iron oxidation, in terms of chemical reactions. When irradiating blood samples with a laser, it leads to the generation of free radicals and lipid peroxide products, especially in the presence of blood cells red, as this supports the hypothesis that states that the effect of photocatalysis after irradiation at a wavelength of 660 nm is nothing but a light interaction with hemoglobin leading to the production of oxygen free radicals. In this study, it was found that the low energy laser (LLL) converts iron (Fe+2) to iron (Fe+3), making hemoglobin unable to carry oxygen as it produces large and uncontrolled amounts of Met-Hb. The study also found that the absorbance of Met-Hb at wavelength 532nm is 60% of what it is for non-oxidized hemoglobin (oxy-Hb), while it was found that the absorbance of Met-Hb at wavelength 632nm is approximately 27 times higher than it is for oxy-Hb It has also been proven that the first changes that occur in the blood sample after exposure to the laser beam are the occurrence of a chemical change that includes the conversion of oxygenated hemoglobin (Oxy-Hb) to Met-Hb
Keywords: laser; hemoglobin; blood; iron